The Influence of Managerial Ownership, Institutional Ownership and Investment Opportunity Set (IOS) on Sharia-Based Dividend Policy - Cindy Septiana; Nur Asmilia (LPPM Universitas Terbuka, 2024)
The research aims to determine and analyze the influence of managerial ownership, institutional ownership, and investment opportunity set (ios) on dividend policies in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period from 2017 to 2022. This research uses a quantitative approach or data which is numbers. The samples used in this study are 6 energy sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2022 using purposive sampling techniques. The data used is secondary data in the form of annual reports from each company that are sampled in the study. The analysis of the results of this study uses the help of the Eviews 12 Student Version Lite software application. The results of this study show that Managerial Ownership partially affects Dividend Policy, Institutional Ownership partially has no effect on Dividend Policy, Investment Opportunity Set (IOS) partially has no effect on Dividend Policy and simultaneously Managerial Ownership, Institutional Ownership and Investment Opportunity Set (IOS) have an effect on Dividend Policy/